A deep dive into giant viruses - Jônatas Santos Abrahão (npj Viruses)
Giant viruses are a complex and diverse group infecting organisms from unicellular eukaryotes to animals. From the characterization of novel viruses to the development of advanced bioinformatic tools for taxonomy and classification, these collection of papers highlights the dynamic nature of giant virus research, uncovering new aspects of their diversity, environmental roles, and evolutionary complexity.